Royal Award Prize Winner of the Danish Academy of Sciences (Chemical Engineering) - Savva, Petros G. (My University, 2026)
The Royal Danish Academy of Sciences and Letters: Copenhagen, Copenhagen, DK
Keywords: Sciences